Mom Back to Work... Breastfeeding is Possible! - Ovando-Diego, Liliana; Hinojosa-García, Abigail; Hernández-Castellanos, Felipe DJ; Zurutuza-Lorméndez, Jorge I. (Atención Familiar, 2023)
Communication with the patient